Development and validation of interactive creativity task platform - Wu, Ching-Lin; Su, Yu-Der; Chen, Eason; Chen, Pei-Zhen; Chang, Yu-Lin; Chen, Hsueh-Chih (Frontiers in Psychology, 2022)
Co-creativity focuses on how individuals produce innovative ideas together. As few studies have explored co-creativity using standardized tests, it is difficult to effectively assess the individual’s creativity performance within a group. Therefore, this study aims to develop a platform that allows two individuals to answer creativity tests simultaneously. This platform includes two divergent thinking tasks, the Straw Alternative Uses Test and Bottle Alternative Uses Test, and Chinese Radical Remote Associates Test A and B, which were used to evaluate their open- and closed-ended creative problem-solving performance. This platform has two modes: single-player mode and paired-player mode. Responses from 497 adults were collected, based on which the fluency, flexibility, and originality of divergent thinking were measured. This research also developed a computer scoring technique that can automatically calculate the scores on these creativity tests. The results showed that divergent thinking scores from computer-based calculation and manual scoring were highly positively correlated, suggesting that the scores on a divergent thinking task can be calculated through a system that avoids time-consuming, uneconomical manual scoring. Overall, the two types of tests on this platform showed considerable internal consistency reliability and criterion-related validity. This advanced application facilitates the collection of empirical evidence about co-creativity.